Properties of Neutrosophic κ- bi-ideals in near-subtraction semigroups - B. Elavarasan; G. Muhiuddin; Y. B. Jun; K. Porselvi (Neutrosophic Sets and Systems)
This paper presents the concept of neutrosophic κ-bi-ideals within the framework of nearsubtraction semigroups and explores the associated findings. The concept of neutrosophic intersections is explored. In addition, we establish some results regarding the homomorphic preimage of a neutrosophic κ-biideal in near-subtraction semigroups.